Oral Therapy Using a Combination of Nanotized Antimalarials and Immunomodulatory Molecules Reduces Inflammation and Prevents Parasite Induced Pathology in the Brain and Spleen of P. berghei ANKA Infected C57BL/6 Mice - Mukherjee, Sitabja; Ray, Gopesh; Saha, Bhaskar; Kar, Santosh K. (Frontiers in Immunology, 2022)
In malaria, anti-parasite immune response of the host may lead to dysregulated inflammation causing severe neuropathology arising from extensive damage to the Blood Brain Barrier (BBB). Use of anti-malarial drugs alone can control parasitemia and reduce inflammation but it cannot reduce pathology if chronic inflammation has already set in. In the present study, we have tested the efficacy of a new oral artemsinin based combination therapy (ACT) regimen using a combination of anti-malarial compounds like nanoartemisinin and nanoallylated-chalcone9 [{1-(4-Chlorophenyl)-3-[3-methoxy-4-(prop-2-en-1-yloxy) phenyl]-prop-2-en-1-one}]given together with anti-inflammatory-cum- anti-malarial compounds like nanoandrographolide and nanocurcumin to C57BL/6 mice infected with P. berghei ANKA. Untreated infected mice developed Experimental Cerebral Malaria (ECM) and died between 10 to 12 days after infection from severe BBB damage. We observed that oral treatments with nanoartemisinin or nano allylated chalcone 9 or nanoandrographolide alone, for 4 days after the onset of ECM, delayed the development of severe neurolopathology but could not prevent it. Nanocurcumin treatment for 4 days on the other hand, prevented damage to the BBB but the mice died because of hyperparasitemia. A single time oral administration of our ACT controlled blood parasitemia and prevented damage to the BBB, but recrudescence occurred due to persistence of parasites in the spleen. However the recrudescent parasites failed to induce ECM and BBB damage, leading to prolonged survival of the animals. A second time treatment at the start of recrudescence led to complete parasite clearance and survival of mice without pathology or parasitemia for 90 days. FACS analysis of spleen cells and gene expression profile in brain and spleen as well as quantitation of serum cytokine by ELISA showed that P. berghei ANKA infection in C57Bl/6 mice leads to a Th1-skewed immune response that result in severe inflammation and early death from ECM. Oral treatment with our ACT prevented a heightened pro-inflammatory response by modulating the Th1, Th2 and Treg immune responses and prevented ECM and death.